Impact of conservation practices on soil quality and ecosystem services under diverse horticulture land use system - Rathore, Avinash Chandra; Singh, Charan; Jayaprakash, J.; Gupta, Anand Kumar; Doharey, Vijay Kumar; Jinger, Dinesh; Singh, Deepak; Yadav, Devideen; Barh, Anupam; Islam, Sadikul; Ghosh, Avijit; Kadam, Darshan; et al. (Frontiers in Forests and Global Change, 2023)
The 20 years study investigated the effects of conservation practices (CP) and farmers' practices (FP) on various soil quality parameters, yield, and economics of horticultural land use systems. CP demonstrated significant improvements in soil organic carbon (SOC), available nitrogen (N), phosphorus (P), and potassium (K) compared to FP. Horticultural systems exhibited higher SOC, available N, and P content compared to FP, with substantial variations among different fruit species.CP also enhanced soil quality index, functional diversity, culturable microbial populations, enzyme activity, and soil microbial biomass carbon (SMBC) compared to FP. It was observed that the SMBC values were 25.0-36.6% and 4.12-25.7% higher in 0-15 cm and 15-30 cm, respectively under CP compared to FP for all the land use systems. In CP, dehydrogenase activity (DHA) activities in surface soils were 9.30 and 7.50 times higher under mango and citrus-based horticultural systems over FP. The CP adopted in aonla, guava, mango, litchi, and citrus-based horticultural system increased SOC by 27.6, 32.6, 24.4, 26.8, and 22.0% respectively, over FP.Canopy spread, fruit yield, litter yield, and soil moisture were significantly higher in fruit-based horticultural systems under CP. Economic viability analysis indicated higher net present values (NPV), benefit-cost ratio (BCR), and shorter payback periods (PBP) for horticultural land use systems under CP. Principal component analysis (PCA) revealed that CP had a more positive influence on soil parameters, particularly DHA, acid and alkali phosphatase activity, available N, P, and K, soil microbial load, and organic carbon. The maximum ecosystem services were contributed through mango based land uses among all land uses. Mango-based horticultural systems exhibited the least impact from both CP and FP, while peach-based systems were most affected by CP.Overall, the findings highlight the benefits of conservation practices in improving soil quality, microbial populations, enzyme activity, and crop productivity in horticultural systems.